INVESTIGATION OF CONSUMERS 'ORGANIC FOOD PURCHASES IN THE CONTEXT OF THE RELATIONSHIP OF PERSONAL VALUES AND INDIVIDUAL FACTORS - TÜKETİCİLERİN ORGANİK GIDA SATIN ALMA NİYETLERİNİN KİŞİSEL DEĞERLER İLE BİREYSEL FAKTÖRLER İLİŞKİSİ BAĞLAMINDA ARAŞTIRILMASI* - Aysel Erciş; Tuğba Yıldız; F.görgün Deveci (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The aim ofthis research was to determine the premises of the personal values affectingthe organic product selection of consumers and to analyze the effect ofenvironmental, price and health consciousness on the attitude towards purchase.The results of this research show that while personal values are effective onindividual factors, health and environmental consciousness, which are among theindividual factors, have an effect on the attitude towards purchase. However,the dimension of price consciousness does not have an effect on the attitudetowards purchase. Furthermore, the findings of the research revealed that theattitude towards purchase has an effect on purchase intention. Consequently,the subjective norm has a moderator effect between the purchase intention andthe attitude towards purchase.